A novel regeneration of iron citrate solution by biooxidation of iron-oxidizing bacteria. (1st November 2014) - Wang, Y J; Li, D P; Liu, C; Zhan, G Q; He, X H
Abstract: Liquid phase oxidation process using chelated iron solution is among the most promising techniques for the hydrogen sulfide removal due to its double advantage of waste minimization and resource recovery. Regeneration of chelated iron is a core reaction in this process. Regeneration of chelated iron in acidic solution is very difficult. In this paper, a novel regeneration of iron citrate in acidic solution by biooxidation of iron-oxidizing bacteria was reported firstly. By using such a process, the influence of iron-oxidizing bacteria on the regeneration rate was investigated. The results demonstrated the regeneration rate with the new technology was increased significantly. The process may contribute to the biooxidation of iron-oxidizing bacteria. Application of this novel process increased the regeneration rate under the optimum conditions, suggesting the iron citrate regeneration process may be a feasible and economical method in application.